Tuning the size and the optical properties of ZnO mesocrystals synthesized under solvothermal conditions - Distaso, Monica; Segets, Doris; Wernet, Ruth; Peukert, Wolfgang; Klupp Taylor, Robin (Nanoscale, 2012)
Mesocrystals are a promising class of nanomaterials enabling new optical and mechanical properties due to their three dimensional organization of primary crystallites sharing a common crystallographic orientation. In the present article, the influence of process parameters such as temperature profile and stirring on the primary and secondary size of ZnO mesocrystals synthesized under solvothermal conditions has been investigated. In general, small but noticeable lattice strain is introduced to the particles during the synthesis process. Additionally, with increasing mass transport the fusion of primary crystallites due to coarsening is enhanced. A closer analysis revealed an influence of the polymer chain length on the final particle structure throughout different hierarchical levels. Based on our findings a reaction mechanism with nucleation and growth taking place embedded in poly-N-vinylpyrrolidone (PVP), followed by a polymer-mediated step of oriented aggregation and subsequent coarsening is proposed. In consequence, the careful control throughout all hierarchical levels of particle synthesis allows fine-tuning of the optical properties of ZnO mesocrystals which show a high UV absorption and minimal scattering in the visible region. © 2012 The Royal Society of Chemistry.